Empowering Deaf Children to Indonesian Cultural Literacy Through VR Box and Applications - Rahayu, Sri; Rahayu, Poppy Sonia (Journal of Education for Sustainability and Diversity, 2025)
The purpose of this empowerment program is to increase the knowledge of deaf students with disabilities regarding the diversity of Nusantara culture and skills in using technology appropriately. This is adjusted to the partner's problem, namely the low literacy of Nusantara culture of grade 4 and 5 students in the subject of art and culture material. This program uses learning media in the form of VR Box and the Lidantara application which contains 3D animations with 360o views and is equipped with sign language videos and subtitles. The implementation method consists of preparation, implementation, closing, evaluation of activities, and preparation of reports. The results obtained from this empowerment activity are changes in student knowledge that can be seen from the results of the pre-test and post-test (from 46% to 97%) as well as sharing session activities where students can re explain cultural material in a coherent, clear, and comprehensive manner.